THERMAL STRAIN AND EXPANSION COEFFICIENT OF PbSb ALLOY UNDER STATIC AND DYNAMIC LOADING - Rammo, N N; Abd Al- Razak, A H (Al-Nahrain Journal of Science, 2010)
Thermal mechanical behavior of PbSb alloy subjected to static and dynamic loading inthe temperature range 30-200 oC and different loading schemes has been investigated. Thetake up strain is Hookian up to 100 oC and transfer to creep behavior for higher temperatures(<100-200 0C) and loads as penetration of the applied load through the alloy sample prevails due tothe transformance of some solidous phase to liquidous phase near the eutectic temperature. Thestrain rate sensitivity factor "m"-value serves to monitor the thermal strain and its effect on theoverall strain thermal and mechanical. Thermal expansion coefficient is found to remain nearlyunchanged up to certain temperature regardless of the applied stress. This may partly due to thecompensation between extension and penetration such that the net change becomes insignificant. Itis suggested that the dimensional stability is largely affected by excessive loading stress rather thanby environmental temperature. PbSb